Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.envres.2020.109554
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of heavy metal contaminated soil by biodegradable chelator–induced washing: Efficiencies and mechanisms

Abstract: Biodegradable chelators (BCs) are promising substitutes for conventional washing agents in the remediation of heavy metal contaminated soil with strong complexing ability and less cost. However, great challenges for the applications of BC-assisted washing still exist, such as the assessment of the factor affecting the efficiency of metal removal and the unclear of the metal removal mechanism. Batch washing was therefore explored to evaluate the potential for four BCs for removing Cd, Pb, and Zn from polluted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(28 citation statements)
references
References 68 publications
1
27
0
Order By: Relevance
“…Decreasing heavy metal concentrations is a crucial objective for remediation of soil for its future reuse. Much more attention should be paid to the environmental risks posed by the presence of mobile metal fractions [ 61 ]. The advantage of using TA is that it decreases metal mobility (MF), defined as the ratio of the metal concentration in the F1 fraction to the sum of the metal concentrations in the F1, F2, F3, and F4 fractions [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Decreasing heavy metal concentrations is a crucial objective for remediation of soil for its future reuse. Much more attention should be paid to the environmental risks posed by the presence of mobile metal fractions [ 61 ]. The advantage of using TA is that it decreases metal mobility (MF), defined as the ratio of the metal concentration in the F1 fraction to the sum of the metal concentrations in the F1, F2, F3, and F4 fractions [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Feng et al [83] used ethylenediamine tetra (methylene phosphonic acid) (EDTMP) and polyacrylic acid (PAA) for soil washing, and tried to optimize operative conditions and reduce ecological risks and toxicity. The same was done by Wang et al [84] who studied four types of acids that are less toxic and more biodegradable than EDTA, namely iminodisuccinic acid (ISA), glutamate-N,N-diacetic acid (GLDA), glucomonocarbonic acid (GCA) and polyaspartic acid (PASP). They demonstrated that these acids are more biodegradable but less effective than EDTA.…”
Section: Chemical Soil Washingmentioning
confidence: 92%
“…In the treatment of contaminated media, the S/L ratio is an important parameter that affects both the overall removal and the extraction of contaminants, as well as the amount of residual wash water [33,53]. Optimization using different S/L ratios was investigated to ensure this treatment's suitability for various contaminated kaolin deposits.…”
Section: Effect Of S/l Ratiomentioning
confidence: 99%